Volume Changes and Mechanical Properties of Expansive Mudstone below Canals under Wet-Dry/Wet-Dry-Freeze-Thaw Cycles - Rui Zhu; Ying-hao Huang; Zhu Song; Feng Zhou (Advances in Civil Engineering)
The complex environment in northern China is the main reason for degradation of expansive mudstone below the canals, which resulted in instability and damage of canal slopes. In this study, a serial of laboratory tests was conducted to explore the volume changes and mechanical behaviors of expansive mudstone below the canals in Xinjiang. The experimental program includes wet-dry (WD) and wet-dry-freeze-thaw (WDFT) tests, volume measurement, and unconfined compression tests. The test results show that during the WD cycles, the volume changes of expansive mudstones with a higher dry range would be more significant. The freeze-thaw process in the WDFT cycles resulted in a decrease of volume change ranges when the expansive mudstones had a relatively smaller dry range and a slight increase of volume change ranges when the expansive mudstones had a relatively larger dry range. In the meantime, the stress-strain relationships of expansive mudstones with different dry ranges all presented strain softening under the cycles of WD or WDFT. The first cycle resulted in a significant decrease of failure strength. After seven WD/WDFT cycles, the failure strength of expansive mudstones with different dry ranges decreased by 37.2%∼59.1%. In addition, the freeze-thaw process in the WDFT cycles promoted the softening of the stress-strain relationships and aggravated the failure strength attenuation of expansive mudstones. Through this study, we expect to provide a preliminary basis for the construction and maintenance of expansive mudstone canals in Xinjiang.